Mentalization and attachment in educational relationships at primary school - Valle, Annalisa; Rinaldi, Teresa; Greco, Andrea; Pianta, Robert; Castelli, Ilaria; Marchetti, Antonella (Ricerche di Psicologia - Open Access, 2022)
Mentalization is a key social ability that develops from infancy to adulthood, starting from early familiar attachment relationships. Children experience several contexts, in particular, educational ones such as school, where they build new attachment relationships with teachers. Although the amount of research on the links between mentalization and attachment has been increasing in recent years, there is still little evidence on the teacher-child relationship from a mentalization perspective. Moreover, only few studies focus on middle childhood, a crucial age for building positive school relationships. This study aims to investigate the possible effects of some measures of teachers’ mentalization, namely, mind-mindedness and mentalised affectivity, and of pupils’ representation of the educational attachment relationship on the mentalization abilities of children aged 8 to 10. The results show that a teacher’s tendency to describe a pupil through physical comments and not mental comments, and her/his ability to use autobiographical memory to interpret the present emotional experience, impact children’s mentalization abilities. This highlights the important role of the teacher in the construction of a class climate that supports pupils’ mentalization.